Combining rational choice and evolutionary dynamics: The indirect evolutionary approach - Manfred Königstein; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
In this study we propose a formal framework for the indirect evolutionary approach as initiated by Güth and Yaari (1992). It allows to endogenize preferences and to study their evolution. We define two-player indirect evolutionary games with observable types and show how to incorporate symmetric as well as asymmetric situations. We show how to apply solution concepts that are well known from game theory and evolutionary game theory to solve these games. For illustration we include two examples.
urn:nbn:de:kobv:11-10046269
Keywords: 330